G2P1A0 37-38 Weeks Pregnant with Cephalopelvic Disproportion, Previous Caesarean Section Scar and Anemia: Risk Factors, Prevention and Management - Case Report - Gultom, Abitmer; Vilanda Sisthaningrum, Ni Made Evina; Prihantini, Nur Nunu (Jurnal KESANS : Kesehatan dan Sains, 2025)
Introduction: Cephalopelvic disproportion (CPD) is a labor-related condition caused by a mismatch between fetal size and maternal pelvic capacity, resulting in obstructed labor and potential maternal-fetal complications. It may arise from pelvic contraction, excessive fetal growth, or a combination of both. Objective: This study aims to report a case of cephalopelvic disproportion with a history of previous cesarean section and anemia in a 29-year-old pregnant woman. Method: A descriptive case-report approach was used. Clinical data were collected from medical records, including patient history, physical examination, laboratory results, and obstetric management procedures. Result and Discussion: The patient, gravida 2 para 1 abortus 0, presented with abdominal tightening, visual disturbances, and a known history of narrow pelvis and previous cesarean delivery. Examination confirmed cephalopelvic disproportion with anemia. Labor progression was stagnant, indicating mechanical obstruction. Cesarean section was performed successfully, and pharmacological treatment was administered to manage anemia and postoperative recovery. Conclusion: This case illustrates the importance of early identification and multidisciplinary management of cephalopelvic disproportion in patients with previous cesarean section and anemia to prevent maternal and neonatal complications